Breaking Barriers: Female Traditional Leadership and the Pursuit of Inclusive Development - Telly Muriany; Victor Sanjak Ruhunlela (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2025)
This study analyzes the leadership of the female traditional leader (Raja Ina), Janse Tresia Leimena, in promoting inclusive development in Negeri Ema, Ambon. Using a qualitative case study method involving interviews, observation, and document analysis, the research finds that her transformational-charismatic leadership style characterized by effective communication, empathy, and an inspiring vision successfully enhanced community participation in supporting vulnerable groups. The main constraints include patriarchal bias within the traditional structure, limited budget, and bureaucratic challenges. The study concludes that indigenous women's leadership has significant potential to act as a catalyst for inclusive development, provided it is supported by multi-stakeholder collaboration and context-responsive policies.